Quantifying Magnetic Anisotropy of Series of Five‐Coordinate CoII Ions: Experimental and Theoretical Insights - Thangaraj, Vijaya; Sartini, Daniele; Borah, Dipanti; Chauhan, Deepanshu; Sharma, Vasudha; Sorace, Lorenzo; Rajaraman, Gopalan; Perfetti, Mauro; Shanmugam, Maheswaran (Advanced science, 2025)
Stabilizing large easy‐axis type magnetic anisotropy in molecular complexes is a challenging task, yet it is crucial for the development of information storage devices and applications in molecular spintronics. Achieving this requires a deep understanding of electronic structure and the relationships between structure and properties to develop magneto‐structural correlations that are currently unexplored in the literature. Herein, a series of five‐coordinate distorted square pyramidal CoII complexes [Co(L)(X2)].CHCl3 (where X = Cl (1), Br (2), or I (3)) is reported, all exhibiting easy‐axis magnetic anicotropy. The size of the zero field splitting axial parameter (D) is quantitatively determined (1 = −72; 2 = −67 and 3 = −25 cm−1) using a cantilever torque magnetometry which is further firmly supported by magnetic susceptibility, and EPR measurements. The study of the magnetization relaxation dynamics reveals field‐induced slow relaxation of magnetization due to the predominant Raman relaxation process. Theoretical calculations on 1–3 and optimized model complexes of 1 reveal insights into the electronic structure and highlight the impact of steric and electronic effects on modulating the D values. Overall, the studies reported pave the way for designing a new generation of CoII complexes with enhanced  axiality and a lower rhombicity. We successfully quantify the zero field splitting parameter (D) in a series of five‐coordinate CoII complexes, [Co(L)(X2)]∙CHCl3 (X = Cl (1), Br (2), I (3)) using torque magnetometry, while highlighting the role of halides in modulating D values. Additionally, ab initio calculations provide insights into the electronic structure and the steric and electronic effects influencing D in these complexes.